Effects of Probiotic Treated Pomegranate Residue on Growth Performance, Immunity and Microbiome in the Intestines of Broilers - Ahmed, Sonia T.; Mun, Hong-Seok; Yang, Chul-Ju (International Journal of Poultry Science, 2025)
Objectives: This research was undertaken to assess the effect of probiotic treated pomegranate residue (PPR) on growth performance, serum immunoglobulins, intestinal and excreta microbiome, and excreta harmful gas emission in broilers. Materials and Methods: A total of 128 day-old Ross-308 chicks were randomly assigned to 4 treatment groups, each consisting of 4 replicates of 8 birds. The experimental diets were formulated to supply 0, 0.5, 1.0 and 2.0% of PPR and were fed for 35 day. Results: Dietary inclusion of PPR linearly increased the weight gain of broiler, while reduced FCR by almost 0.10 points without affecting the feed intake (p